KELAYAKAN PENUNTUN PRAKTIKUM SUBMATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN DENGAN TAMBAHAN METODE REPLIKA - Dia Widi Hastika; Entin Daningsih; Reni Marlina (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the feasibility of laboratory work guide on structure and function of plant tissue submaterial in class XI High school with additional of replica method. This research form is descriptive with two stages, namely instrument validation and media validation. The instrument validator consisted of two Biology Education lecturers and one high school biology teacher. The laboratory work guide validator consisted of two Biology Education lecturers and three high school biology teachers who conducted 2013 curriculum. Data were analyzed using Lawshe method with the Content Validity Ratio (CVR) and Content Validity Index (CVI) formulas. The results of the validation showed that the instrument was feasible to be used and the results of the laboratory work guide validation obtained CVR and CVI values up to 0.99 which corresponded to Lawshe's minimum CVI value for five validators so that the laboratory work guide was declared valid and feasible to use as learning media on class XI for structure and function of plant tissue submaterial in High school. Keywords: Feasibility, Laboratory Work Guide, Validation.